2007
DOI: 10.1097/01.rct.0000236420.28137.aa
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Venous Congestion After Right-lobe Living-donor Liver Transplantation

Abstract: A hypoattenuating area of the liver during DP scans indicates severe hepatic congestion and is correlated with hyperbilirubinemia and a high mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…However, in the field of LDLT, impairment of liver regeneration of the anterior section has been reported in donors after left hemiliver graft including the MHV . Furthermore, in recipients of a right hemiliver graft without MHV, the congestive rates in the anterior section were 62% to 92%, and the congestion was also highly related to the venous anatomy . In our present study, patients who underwent left hepatectomy including the MHV showed some congestive and dysfunctional areas in the anterior section.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…However, in the field of LDLT, impairment of liver regeneration of the anterior section has been reported in donors after left hemiliver graft including the MHV . Furthermore, in recipients of a right hemiliver graft without MHV, the congestive rates in the anterior section were 62% to 92%, and the congestion was also highly related to the venous anatomy . In our present study, patients who underwent left hepatectomy including the MHV showed some congestive and dysfunctional areas in the anterior section.…”
Section: Discussionsupporting
confidence: 40%
“…Computed tomography and MRI can be used to evaluate congestion in the liver graft after transplantation or in the remnant liver of donors . Congestion appeared as high intensity on T2‐weighted MRI .…”
Section: Discussionmentioning
confidence: 99%
“…Significant RHV stenosis was diagnosed when there was appreciable weakness of pulsatility or changes in the waveform from a triphasic pattern to a biphasic or monophasic pattern on Doppler ultrasonography and there was concurrent noticeable narrowing of the RHV at the anastomosis within the liver graft or at the IVC on CT scans 19. Hepatic venous congestion was indicated by changes in parenchymal perfusion on CT scans, with or without increases in serum levels of hepatic enzymes 20‐22. A CT scan was undertaken promptly when serum levels of hepatic enzymes (aspartate/alanine aminotransferase) increased rapidly to values >500 IU/L at any time after transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…Multiphase contrast enhanced CT, Doppler ultrasonography, and MRI are all used to non-invasively evaluate hepatic venous congestion after liver transplantation [16][17][18]. However, these imaging modalities can hardly provide quantitative measurements of segmental congestion.…”
Section: Perfusion Imaging In Liver Transplantationmentioning
confidence: 99%